Ergogenic effect of beet juice supplementation on physical exercise (Research, Society and Development, 2022)
Beetroot is highly rich in important chemicals and stands out for its high concentration of B vitamins and various nutrients. In its chemical substances, beet has a high concentration of inorganic nitrate (NO₃), a substance used as an ergogenic supplement when related to therapeutic treatments, being a multifunctional physiological signal, essential for health and vascular function. Our body, when subjected to a stimulus, tends to leave its homeostatic state, and the chemical component present in beets, nitrate, will be responsible for activating an effective vasodilation, due to the conversion of nitrate into nitric oxide. The objective of the present study will be to analyze in scientific articles, which relate the effect of supplementation with beetroot juice as a pre-workout, in improving the performance of physical exercise practitioners, and the effects of using beetroot juice as a supplementation strategy for cardiorespiratory resistance, as well as to understand other possible benefits allied to its use with regard to the vasodilator effect, providing greater oxygen supply to the muscle, muscle fatigue.